Pengembangan bahan ajar untuk meningatkan perilaku sosial anak prasekolah melalui kreativitas bahasa - Nurchasanah, Nurchasanah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This research aims to develop teaching materials for kindergarten teachers, PGTK lecturers, and students majoring in PGTK to improve preschoolers’ social behavior through a language creativity approach. Specifically, the objectives of the study were formulated as follows. In the first year, the study aimed (1) to describe (a) the kindergarten curriculum related to the development of children’s social behavior and (b) previous studies on social behavior and its development, and (2) to develop a prototype of the teaching materials. In the second year, the study focused on conducting expert validation and try-out activities. This research employed a Research and Development (R&D) design consisting of the following procedures: (1) planning, theoretical review, and needs analysis; (2) prototype development; (3) evaluation through expert validation and try-out; and (4) product revision. The final product of this study is a prototype of teaching materials entitled Mengembangkan Kecerdasan Sosial Anak melalui Kreativitas Bahasa, intended for kindergarten teachers, PGTK lecturers, and students majoring in PGTK.